Efficiency of Post-Space Irrigation Protocols on the Push-Out Bond Strength of Fiber Post to Post-Space - Soner Şişmanoğlu (Current Research in Dental Sciences, 2025)
Objective: This study aimed to examine how different post-space irrigation protocols influence the push-out bond strength (PBS) of fiber posts to the post-space.Method: The study involved 60 mandibular first premolar teeth with single root. The teeth were divided into two in accordance with the irrigation protocol (n = 30): passive irrigation and sonic irrigation. A self-adhesive resin cement was used for the cementation of fiber posts. One half of the specimens underwent chewing simulation for 250,000 cycles of dynamic loading with thermal cycling. For each tooth, three transversal sections were taken, with each section having a thickness of 2 mm. These sections were collected from the coronal, middle, and apical thirds of the post-place. The PBS in each section was examined using a universal testing device. The collected data were subjected to statistical analysis using three-way ANOVA and Tukey tests, with a significance level set at 5%.Results: The passive irrigation group demonstrated the lowest bond strength (P